Paramedic Application of a Triage Sieve: A Paper-Based Exercise. Issue 1 (14th December 2016) - Cuttance, Glen; Dansie, Kathryn; Rayner, Tim
Abstract: Introduction: Triage is the systematic prioritization of casualties when there is an imbalance between the needs of these casualties and resource availability. The triage sieve is a recognized process for prioritizing casualties for treatment during mass-casualty incidents (MCIs). While the application of a triage sieve generally is well-accepted, the measurement of its accuracy has been somewhat limited. Obtaining reliable measures for triage sieve accuracy rates is viewed as a necessity for future development in this area. Objective: The goal of this study was to investigate how theoretical knowledge acquisition and the practical application of an aide-memoir impacted triage sieve accuracy rates. Method: Two hundred and ninety-two paramedics were allocated randomly to one of four separate sub-groups, a non-intervention control group, and three intervention groups, which involved them receiving either an educational review session and/or an aide-memoir. Participants were asked to triage sieve 20 casualties using a previously trialed questionnaire. Results: The study showed the non-intervention control group had a correct accuracy rate of 47%, a similar proportion of casualties found to be under-triaged (37%), but a significantly lower number of casualties were over-triaged (16%). The provision of either an educational review or aide-memoir significantly increased the correct triage sieve accuracy rate to 77% and 90%, respectively. Participants who received both the educational review and aide-memoir had an overall accuracy rate of 89%. Over-triaged rates were found not to differ significantly across any of the study groups. Conclusion: This study supports the use of an aide-memoir for maximizing MCI triage accuracy rates. A "just-in-time" educational refresher provided comparable benefits, however its practical application to the MCI setting has significant operational limitations. In addition, this study provides some guidance on triage sieve accuracy rate measures that can be applied to define acceptable performance of a triage sieve during a MCI. G Cuttance, K Dansie, T Rayner .Paramedic application of a triage sieve: a paper-based exercise .Prehosp Disaster Med .2017 ;32 (1 ):3 –13 .